Dynamic tank in series modeling of direct internal reforming SOFC - Hosseini, Shahin; Vijay, Periasamy; Ahmed, Khaliq; Tade, Moses; Pareek, Vishnu; Utikar, Ranjeet (2017)
A dynamic tank in series reactor model of a direct internally reforming solid oxide fuel cell is presented and validated using experimental data as well as a computational fluid dynamics (CFD) model for the spatial profiles. The effect of the flow distribution pattern at the inlet manifold on the cell performance is studied with this model. The tank in series reactor model provides a reasonable understanding of the spatio-temporal distribution of the key parameters at a much lesser computational cost when compared to CFD methods. The predicted V-I curves agree well with the experimental data at different inlet flows and temperatures, with a difference of less than ±1.5%. In addition, comparison of the steady-state results with two-dimensional contours from a CFD model demonstrates the success of the adopted approach of adjusting the flow distribution pattern at the inlet boundaries of different continuous stirred tank reactor compartments. The spatial variation of the temperature of the PEN structure is captured along with the distributions of the current density and the anode activation over-potential that strongly related to the temperature as well as the species molar fractions. It is found that, under the influence of the flow distribution pattern and reaction rates, the dynamic responses to step changes in voltage (from 0.819 to 0.84V), fuel flow (15%) and temperature changes (30°C), on anode side and on cathode side, highly depend on the spatial locations in the cell. In general, the inlet points attain steady state rapidly compared to other regions.